Study on the Utilisation of Internet of Things (IoT) Technology in Modern Agriculture Management - Sri Nofriyanti; Aulia Sri Hipma (Agriculture Journal, 2024)
Internet of Things (IoT) technology has emerged as a potential solution to solve various problems in modern agriculture. This study uses a quantitative-descriptive approach with the aim of describing the application of IoT technology in agricultural management and identifying factors that influence its successful implementation. This approach is also complemented by a qualitative study to explore farmers' and experts' insights on the challenges and benefits of implementing IoS in the agricultural sector. The results show that the majority of informants have positive perceptions of the benefits of the application, especially in the form of improved water and fertiliser use efficiency, increased crop yields, and labour and time savings. The majority of farmers with a good understanding of the technology have a positive perception of its benefits, with 15 and 20 farmers rating it as very useful, respectively. However, there are major obstacles, namely the need for adequate infrastructure, training for farmers, and subsidising implementation costs. Theories of technological efficiency, technology adoption, and resource management support these findings, which suggest that successful implementation depends on infrastructure readiness as well as access and support for farmers.